Clinico-hematological Study of Theileriosis in Gir and Jaffrabadi Calves - Brahmbhatt, NN; Kumar, B; Thakre, BJ; Parmar, VL; Choravada, DR; Patel, JA (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The present study was undertaken to know the hematological alteration in Theileria infected Gir and Jaffrabadi calves in and around  Junagadh, Gujarat. Young calves (less than one year of age) with suspected clinical signs of hemoprotozoan infection, presented at  the Veterinary Clinical Complex of the College in Junagadh, were taken in this study. Out of 64 suspected cases examined, 13 (20.31%)  were found positive for Theileria infection by microscopic blood smear examination. The prevalence of Theileria infection was more in  the rainy season (27.27%) followed by summer (26.31%) and least in the winter season (8.69%). Theileria infection was significantly (p
Keywords: Gir cattle; Hematology; Jaffrabadi buffalo; Prevalence; Theileria; Young calves